2012
DOI: 10.1111/j.1471-4159.2012.07773.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the efficacy of statins in animal stroke models: a meta‐analysis

Abstract: J. Neurochem. (2012) 122, 233–243. Abstract Protective effects of statins have been well documented for stroke therapy. Here, we used a systematic review and meta‐analysis to assess these evidences. We identified 190 studies using statin treatment in stroke animal models by electronic searching. From those, only studies describing ischemic occlusive stroke and reporting data on infarct volume and/or neurological outcome were included in the analysis (41 publications, 1882 animals). The global estimate effect w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 38 publications
(37 reference statements)
1
53
0
1
Order By: Relevance
“…The methodological quality of individual studies was assessed based on a checklist modified from the Collaborative Approach to Meta-Analysis and Review of Animal Data from Experimental Studies (CAMARADES) as previously described with minor modification [22, 23]. The checklist was comprised of 10 items: (1) peer reviewed publication; (2) presence of randomization of subjects into treatment groups; (3) assessment of dose-response relationship; (4) blinded assessment of behavioural outcome; (5) monitoring of physiological parameters such as body temperature; (6) calculation of necessary sample size to achieve sufficient power; (7) statement of compliance with animal welfare regulations; (8) avoidance of anaesthetic agents with marked intrinsic neuroprotective properties (e.g., ketamine); (9) statement of potential conflicts of interest; (10) use of a suitable animal model.…”
Section: Methodsmentioning
confidence: 99%
“…The methodological quality of individual studies was assessed based on a checklist modified from the Collaborative Approach to Meta-Analysis and Review of Animal Data from Experimental Studies (CAMARADES) as previously described with minor modification [22, 23]. The checklist was comprised of 10 items: (1) peer reviewed publication; (2) presence of randomization of subjects into treatment groups; (3) assessment of dose-response relationship; (4) blinded assessment of behavioural outcome; (5) monitoring of physiological parameters such as body temperature; (6) calculation of necessary sample size to achieve sufficient power; (7) statement of compliance with animal welfare regulations; (8) avoidance of anaesthetic agents with marked intrinsic neuroprotective properties (e.g., ketamine); (9) statement of potential conflicts of interest; (10) use of a suitable animal model.…”
Section: Methodsmentioning
confidence: 99%
“…However, in this case quality-score was negatively related to effect size (Baryan et al, 2012;Garcia-Bonilla et al, 2012). Matthan et al (2005) reported a meta-analysis on the effect of omega-3 fatty acids on cardiac arrhythmias .…”
Section: Internal Validity Of Animal Researchmentioning
confidence: 81%
“…However, there was no association between an initiation of statin treatment after stroke and functional outcome in our study, probably because that timing to initiate statin therapy after stroke would be varied among patients. Efficacy of statin treatment to reduce stroke size has been shown to decrease as delay in initiation of the treatment after stroke increases [36]. The effect of initiation of statin treatment after stroke could be explored by randomized trials with larger numbers of participants; however, this was beyond the scope of the current study.…”
Section: Discussionmentioning
confidence: 99%